2017
DOI: 10.18535/jmscr/v5i3.61
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evaluation of Internal Derangements of Knee Joint

Abstract: Background-The knee is one of the most commonly involved joint in the external injuries. Internal derangement of knee (IDK) joint is a common cause of morbidity in the young

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…The MM tear was more common (57%) than LM tears (36%) in our study which corresponded with study by La Prade et al 24 who reported that medial meniscal tears are twice as common as lateral meniscal tears. MCL tear was observed in 10% patients similar to the study by Josey Verghese et al 23 who found MCL tear in 13% patients, however, the incidence of grades of MCL tear was different in all studies which may be attributed to less number of patients with MCL tear. In our study, MCL tears (10%) were found to be more common than the LCL tear (7%).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The MM tear was more common (57%) than LM tears (36%) in our study which corresponded with study by La Prade et al 24 who reported that medial meniscal tears are twice as common as lateral meniscal tears. MCL tear was observed in 10% patients similar to the study by Josey Verghese et al 23 who found MCL tear in 13% patients, however, the incidence of grades of MCL tear was different in all studies which may be attributed to less number of patients with MCL tear. In our study, MCL tears (10%) were found to be more common than the LCL tear (7%).…”
Section: Discussionsupporting
confidence: 82%
“…However, Singh JP et al studied 173 patients and found ACL tear in 78 patients (Partial tear-66.6% and complete tear -33%). Similar study by Josey Verghese et al 23 on 69 patients found ACL tear in 49 patients (53.06% were partial tears and 46.93% were complete tear). Our study result is in contrary to most of the previous studies where they have found the incidence of partial tear more as compared to complete tear.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation